Eradication of Criminal Acts of Obscenity by Children - Risdayun Limbong (Estudiante Law Journal, 2022)
The purpose of this research is to know and analyze abouthow to eradicate it is an issue that is constantly being debated, one of which is the criminal act of obscenity by children. Sexual crimes committed by children often occur, especially in the jurisdiction of the Boalemo Police, and the factors that cause acts of obscenity committed by minors in the Legal Area of Boalemo Regency are caused by internal (family and gender) and external factors. (environment, internet and liquor as well as low education and economy). Efforts to deal with sexual abuse in the jurisdiction of the Boalemo Police are preventive, repressive, curative, delinquent from a criminological perspective and pre-emtief.